Study on Mathematical Competence and Attitude of Engineering Students - Kocsis, Imre; Sebők-Sipos, Dóra (International Journal of Engineering and Management Sciences, 2017)
Efficiency of the learning process is in the focus of studies dealing with the Hungarian higher education, including engineering education. The efficiency can be evaluated if the required competences are declared and systematically controlled. In this paper the results of a graduate student survey is presented. Students taking part in the survey have got a bachelor’s degree in engineering and are first semester students presently in different engineering master programs. Mathematical thinking ability and creativity, as important competences in studying mathematics were measured with the questionnaire, rather than formulas and complicated calculation methods. Students’ experience in studying and applying Mathematics were asked in the first part of the questionnaire.